Pengaruh Slang TikTok terhadap Penggunan Bahasa Indonesia Dikalangan Remaja - Alvin Fahrezi; Amelia Amelia; Annisa Khairina; Diana Nabila Putri; Nina Ayu Lestari; Syifa Ivanka Namira; Tari Ananda (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2026)
This study examines the influence of TikTok slang on the use of the Indonesian language among teenagers in the contemporary social media era. The rapid expansion of TikTok as a widely used digital platform has contributed to the emergence and dissemination of new linguistic variations that are frequently adopted in everyday communication. The objective of this research is to identify how TikTok slang affects teenagers’ language use, particularly in terms of vocabulary and structure. This study employs a qualitative descriptive method, with data collected through observation and questionnaires administered to active teenage TikTok users. The data are analyzed through stages of data reduction, data display, and conclusion drawing to ensure systematic interpretation. The findings reveal that TikTok slang significantly shapes teenagers’ communication patterns, as they tend to incorporate slang expressions into both informal interactions and, to some extent, formal contexts, leading to a shift from standard Indonesian language norms. However, the use of slang also offers positive implications, including the enhancement of linguistic creativity and the development of social identity among teenagers. Therefore, this study highlights the importance of fostering language awareness to encourage the appropriate and context-sensitive use of Indonesian in accordance with established linguistic standards.